Theodicy in the World of the Bible - Laato, Antti; Moor, Johannes C. de (Leiden BRILL, 2003)
Theodicy is traditionally considered the attempt to defend divine justice in the face of God's apparent indifference or hostility toward virtuous people.
Keywords: Bible -- Criticism, interpretation, etc. Bible -- Critique, interprétation, etc. Bible. Bibel Theodicy -- History of doctrines. Middle Eastern literature -- History and criticism. Jewish religious literature -- History and criticism. Rabbinical literature -- History and criticism